Diskresi Hakim dan Perlindungan Anak: Analisis Maqashid Syari’ah terhadap Penolakan Dispensasi Nikah Akibat Hamil di Luar Nikah - Abdul Aziz; Iqbal Subhan Nugraha; Abdul Wafi Muhaimin; Sugeng Aminudin (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2025)
This study aims to examine the legal considerations of religious court judges in denying marriage dispensation requests prompted by premarital pregnancy, specifically analyzing Decision Number 27/Pdt.G/2024/PA.CN through the analytical lens of Maqashid al-Shari’ah. Methodologically, this research employs a qualitative-doctrinal approach utilizing a case-study method to critically evaluate judicial reasoning alongside contemporary child protection frameworks. The findings indicate that the judge’s decision to deny the dispensation request was strictly rooted in a broader systemic paradigm that prioritizes the best interests of the child over immediate socio-cultural pressures or administrative relief. From a Maqashid al-Shari’ah perspective, while premarital pregnancy creates a social emergency, granting an early marriage to unprepared minors poses a more significant risk to their long-term well-being. Therefore, the denial serves as an operational implementation of protecting the soul (hifdh al-nafs), intellect (hifdh al-’aql), and future lineage (hifdh al-nasl) by preventing the perpetuation of unstable family structures and socio-economic vulnerability. Financially and socially, this study contributes valuable insights for legal practitioners and religious authorities by shifting the judicial framework from a purely formalistic administrative response to a substantive, protection-oriented mechanism. Ultimately, these insights offer a balanced and non-technical legal model that effectively reconciles traditional Islamic jurisprudence boundaries with modern civilizational child protection standards.